ANALYSIS OF FACTORS THAT INFLUENCE THE AMOUNT OF REST OF BUSINESS RESULTS (SHU) IN KARYA BHAKTI RAHARJA COOPERATIVE - Dita Agustia; Sihabudin Sihabudin; Syifa Pramudita Faddila (SEAN Institute, 2022)
Karya Bhakti Raharja Cooperative is a savings and loancooperative whose members are employees of BUMN PerumJasa Tirta II Purwakarta office. Its members are all PJT IIemployees and PJT II retirees. The aims of this study are asfollows (1) To determine the effect of the number of members,the number of deposits and the number of loans simultaneouslyon the amount of the remaining operating results at the KaryaBhakti Raharja Cooperative (2) To determine the effect of thenumber of members, the number of savings and the number ofloans partially on the amount the remaining operating resultsin the Karya Bhakti Raharja Cooperative (3) To determine themost dominant variable between the number of members, thenumber of savings and the amount of loans to the amount of theremaining operating results of the Karya Bhakti RaharjaCooperative. This study uses a descriptive verification methodwith secondary data from the 2020 internship report. The dataanalysis technique uses the multiple linear regression method.The results of data analysis show that the number of members,the number of deposits and the number of loans simultaneouslyhave a significant effect on the remaining operating results. Thevariable amount of savings partially has a significantrelationship and influence on the remaining operating results.While the variable number of members and the number ofloans partially do not have a significant relationship andinfluence on the remaining operating results. From the resultsof the study, it is suggested the need to increase membersavings by increasing the number of members through gradualrecruitment. In addition, cooperatives must have a creditanalysis of member loan